A Refined Method to Analyze Insoluble Particulate Matter in Ice Cores, and Its Application to Diatom Sampling in the Antarctic Peninsula - Tetzner, Dieter; Thomas, Elizabeth R.; Allen, Claire S.; Wolff, Eric W. (Frontiers in Earth Science, 2021)
The insoluble particulate matter deposited on ice sheets provide key information to reconstruct past climate. The low concentration of some insoluble particulate matter, such as terrigenous particles and microfossils, challenges the efficiency of the recovery and the representativeness of the results. Here we present a new optimized method to extract, quantify and classify targeted low concentration insoluble particulate matter. Particle recovery rates and particle distribution were investigated using polystyrene particle standards filtered through Polycarbonate membrane filters and subsequently scanned in a scanning electron microscope. Experimental results in continuous and discrete sampling systems reveal consistent trends in the transport and removal of particulate material inside a filtration system. Statistical simulations are used to optimize the sample analyses required to achieve representative results. The analysis of diatoms in ice cores using this new method uncovered their potential to hold valuable climate records from the Antarctic Peninsula region. The data presented here evidences the presence of a measurable amount of marine diatoms with sub-annual variations, highlighting the potential of this record as a seasonal indicator. The new method presented provides an optimized and statistically representative approach for extracting, recovering and analysing micrometre-sized, low-concentration insoluble particulate matter in ice.